Design of Dual Polarized FMCW Radar System With High Gain Lens Antenna for Through-the-Wall Human Detection - Chanhee Lee; Kyung Hwan Park; Hyungju Kim; Jayol Lee; Hyunseok Kim; Kyeong-Han Shin; Jeong-Wook Kim (IEEE Access)
This paper presents the design of a dual-polarized Frequency Modulated Continuous Wave (FMCW) radar system equipped with a high-gain lens antenna for the detection of human targets behind walls. The radar system parameters were designed for through-the-wall human detection, and based on these parameters, both the antenna and radar system were developed accordingly. The proposed radar system harnesses the benefits of dual polarization and a compact lens antenna to enhance the signal-to-noise ratio (SNR), a critical parameter for accurate through-the-wall detection. The lens antenna is engineered to provide wideband and high-gain performance in the X-band while maintaining a compact form factor, effectively addressing the conventional trade-offs between antenna size and performance. Furthermore, the application of polarization synthesis markedly enhances the SNR of the received signal, enabling more reliable detection of multiple human targets through the wall. Experimental validation demonstrates the system’s efficacy in detecting human targets through a wall. The dual-polarization synthesis technique yields substantial improvements in both SNR and detection accuracy in through-the-wall scenarios.